The unique regulation and functions of type III interferons in antiviral immunity - Odendall, Charlotte (Curr Opin Virol, 2015)
Type I interferons (IFNs) were long considered to be the sole IFN species produced by virus-infected cells until the discovery of type III IFNs (IFNλs), decades later. Like type I IFNs, type III IFNs are induced by and protect against viral infections, leading to the initial conclusion that the two IFN species are identical in regulation and biological functions. However, the two systems differ in the tissue expression of their receptor, resulting in different roles in vivo. The unique nature of IFNλs has been further demonstrated by recent studies revealing differences in the regulation of type I and III IFN expression, and how these proteins elicit specific cellular responses. This review focuses on the distinctive features of type III IFNs in antiviral innate immunity.